Treeline and timberline dynamics on the northern and southern slopes of the Retezat Mountains (Romania) during the late glacial and the Holocene. (30th May 2018) - Orbán, Ildikó; Birks, Hilary H.; Vincze, Ildikó; Finsinger, Walter; Pál, Ilona; Marinova, Elena; Jakab, Gusztáv; Braun, Mihály; Hubay, Katalin; Bíró, Tamás; Magyari, Enikő K.
Abstract: To investigate treeline and timberline dynamics in the Retezat Mountains (Romanian Carpathians), late glacial and Holocene sediment sequences from four lakes were studied. The south and north slopes of the mountain range were compared using two lakes from the north flank (Lake Brazi, 1740 m a.s.l. and Lake Gales, 1990 m a.s.l) and two from the south flank (Lake Lia, 1910 m a.s.l. and Lake Bucura, 2040 m a.s.l.). Macrofossil and stomata analyses were performed to assess changes in the local vegetation, supplemented by pollen, charcoal and loss-on-ignition analyses. Our results show that treeline reached Lake Brazi on the northern side during the late glacial (ca. 14, 000 cal yr BP) and then Lake Gales between 11, 000 and 10, 800 cal yr BP. During the early Holocene the upper limit of closed forest, the timberline, reached and passed Lake Brazi and has stayed above it since, but it has never reached Lake Gales at 1990 m a.s.l. The expansion of Larix decidua in the late glacialand early Holocene around Lake Brazi is unique. Stomata and macrofossils of Abies alba are also more abundant in the northern records. On the southern flank, treeline reached Lake Lia at around 12, 000 cal yr BP, and was either very close to or at the elevation of Lake Bucura between ca. 8600 and 3000 cal yr BP. Timberline reached Lake Lia at ca. 8000 cal yr BP, some 3000 years after Lake Brazi, only 170 m lower on the north slope. Local fire events delayed the advance of timberline around Lake Lia in the early Holocene in a dry continental climate. The surrounding forest was dominated by Picea abies with individuals of Pinus cembra and stands of P. mugo until about 3000 cal yr BP when timberline retreated below the lake. Maximum elevation of timberline was attained between ca. 8000 and 3000 cal yr BP, after which it descended in response to climate cooling. Regional climate change appears to be the main driver of treeline dynamics, but it was modified by local climatic differences due to slope aspect. The first signs of human disturbance appeared ca. 4200 cal yr BP, when naturally open areas were used as alpine pastures. Human impact in the treeline ecotone, mainly burning and grazing, was intensified after ca. 2600 cal yr BP, contributing to the widening of the ecotone and the lowering of the timberline.